Building the Foundation of Indonesia’s Digital Economy: Encourging the Adoption of Bitcoin and Blockchain Technology to Increase Financial Inclusion and Efficiency - Wardatussyarifa , Yulia; Ardelia, Nafisa Nabila; Ibrahim, Muhamad Sandy; Zahroh, Fatmawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to promote the adoption of bitcoin and blockchain technology to enhance financial inclusion and efficiency in Indonesia. A mixed-method approach was used, involving qualitative interviews with experts and users of blockchain and bitcoin, as well as quantitative surveys distributed to students and the general public. Findings suggest that these technologies can improve efficiency in the financial sector by reducing costs and improving accessibility, especially for people without access to traditional banking services. However, the successful implementation of blockchain and bitcoin requires proper education on their use. Theoretical implications highlight the role of blockchain in advancing digital financial inclusion, while practical implications point to the need for government regulations and strategies for financial institutions. This research offers insights into supporting digital economic transformation and improving the efficiency of financial services in Indonesia.